Some Socio-Political Factors of Sustainable Development In New Uzbekistan - Utamuradov, Akbar (Indonesian Journal Publisher, 2025)
This study explores the role of the press in cultivating patriotism among Uzbekistan’s border troops. The research aims to assess how media platforms contribute to instilling national values, courage, and civic responsibility in military personnel. A qualitative content analysis approach was applied, analyzing government publications, patriotic campaigns, and historical records. The findings show that military-focused media such as